Impact of lockdown and non-pharmaceutical interventions on the epidemiology of Legionnaires’ disease: Legionnaire’s disease and COVID-19 - Riccò, Matteo (Acta Biomedica Atenei Parmensis, 2022)
Background and aim. In order to cope with the requirements of COVID-19 pandemic and prevent overwhelming of the healthcare systems, during 2020 social distancing measures were proposed, and generalized lockdown. Aim of our study is to ascertain whether non-pharmaceutical intervention did have any impact on the epidemiology of Legionnaires’ disease (LD), a respiratory infectious disease without interhuman spreading.Methods. Official national reports from 4 index countries in European Union (i.e. Germany, France, Italy, and Spain) were retrieved. The study included all cases notified during 2020 COVID-19 outbreak, versus the cases referred during the same period in 2019. Subgroup analyses for hospital-associated and travel-associated LD cases, as well as for lethality estimates were performed.Results. A sustained drop for incidence rate was confirmed, at EU-level (3.5 per 100,000 vs. 5.3 per 100,000) as well as in the national estimates. The decrease was particularly evident in Italy (RR 0.880, 95%CI 0.839 to 0.905), despite a transient surge in notification rates during the month of June, 2020. Subgroup analyses demonstrated a fall in travel-associated cases (-66.8% at EU level), while hospital-associated cases decreased in absolute number when compared to 2019, but where substantially stable in terms when compared to EU estimates. While Case Fatality Ratio increased in comparison with 2019, no significant trend was similarly identified in comparison to EU estimates. Conclusions. Lockdown measures have impacted on the epidemiology of LD in Europe during 2020, but some heterogeneities were identified both across the assessed countries, and the various subgroup. Even though the absolute number of total cases did substantially decrease in 2020 compared to 2019, the effect of non-pharmaceutical interventions was mostly indirect, through a reduced interaction of individuals with environments at potentially high-risk for human infections (e.g. hospitals, accommodation sites, etc.).